2016
DOI: 10.1186/s41200-016-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Holacanthus clarionensis (Pomacanthidae), Stegastes leucorus, and Stegastes acapulcoensis (Pomacentridae) at Magdalena Bay, B.C.S., Mexico

Abstract: Pomacanthids and Pomacentrids are mainly distributed in tropical and subtropical regions, and inhabit shallow rocky and coral reefs. Due to their colorful patterns and unusual body shapes, they have been widely targeted by aquarium fish trade; these species are of great commercial interest. Here we document the occurrence of one Pomacanthid (Holacanthus clarionensis), and two Pomacentrids (Stegastes acapulcoensis, and S. leucorus) north of their reported distribution range during the 2014 warm water period in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…These studies have indicated that the distribution ranges of fish species have expanded, possibly due to climate change given the increase in water temperature that has been mainly reported for the central region of the Gulf of California (García-Morales et al 2017;Robles-Tamayo et al 2018). The presence of the clarion angelfish may have been due to a moderate El Niño during 2009 (https:// ggweather.com/enso/oni.htm) and to the resulting expansion of the distribution of this tropical species into temperate waters (Hernández- Velasco et al 2016). However, we assumed that this specimen either moved to another area in the Gulf of California with more tropical characteristics or died without being able to colonize the site.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have indicated that the distribution ranges of fish species have expanded, possibly due to climate change given the increase in water temperature that has been mainly reported for the central region of the Gulf of California (García-Morales et al 2017;Robles-Tamayo et al 2018). The presence of the clarion angelfish may have been due to a moderate El Niño during 2009 (https:// ggweather.com/enso/oni.htm) and to the resulting expansion of the distribution of this tropical species into temperate waters (Hernández- Velasco et al 2016). However, we assumed that this specimen either moved to another area in the Gulf of California with more tropical characteristics or died without being able to colonize the site.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, participation in scientific processes and the creation of trust between fishers and researchers means that fishers report unusual events. Seven papers have been published on range extensions or first sightings due to information provided by fishers (Martínez-Torres et al, 2014;Fernández-Rivera Melo et al, 2015aHernández-Velasco et al, 2016;López-Fuerte et al, 2018) and fishers were the first to detect hypoxia events in the Pacific Ocean due to shifts in the California Current (Micheli et al, 2012;Boch et al, 2018).…”
Section: Discussionmentioning
confidence: 99%